2021
DOI: 10.1001/jama.2021.12655
|View full text |Cite
|
Sign up to set email alerts
|

Association of Labor Epidural Analgesia With Autism Spectrum Disorder in Children

Abstract: IMPORTANCEA recent cohort study found that epidural analgesia during labor was associated with an increased risk of autism in offspring.OBJECTIVE To investigate if labor epidural increases the risk of autism in offspring. DESIGN, SETTING, AND PARTICIPANTSThis nationwide retrospective cohort study identified all live-born children in Denmark between January 2006 and December 2013. Follow-up commenced at children's first birthday and ended in December 2017. Among 485 093 live-born children, 5915 were excluded be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
74
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(80 citation statements)
references
References 26 publications
6
74
0
Order By: Relevance
“…The PubMed search using our defined search criteria initially yielded 37 citations, of which 15 were directly related to this research question, and 4 presented original data. 3 , 8 , 9 , 10 All 4 studies were included in the meta-analysis and were pooled with the results from our analyses. Results from the meta-analysis yielded a pooled adjusted HR of 1.10 (95% CI, 1.06-1.13) ( Figure 4 ) with a P value from the χ 2 test of .001, suggesting between-study heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…The PubMed search using our defined search criteria initially yielded 37 citations, of which 15 were directly related to this research question, and 4 presented original data. 3 , 8 , 9 , 10 All 4 studies were included in the meta-analysis and were pooled with the results from our analyses. Results from the meta-analysis yielded a pooled adjusted HR of 1.10 (95% CI, 1.06-1.13) ( Figure 4 ) with a P value from the χ 2 test of .001, suggesting between-study heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…The other two studies from Denmark used the same data sources and classifications for ELA and ASD but reported different adjusted hazard ratios [ 16 , 17 ]. The first study conducted by Mikkelsen et al identified all live-born children in Denmark between January 2006 and December 2013 with the offspring follow-up up to December 2017.…”
Section: Resultsmentioning
confidence: 99%
“…In United States, 70% of the expectant mothers receive LEA during their birth-giving ( 8 ), and it is demonstrated to be safe for the newborns ( 9 ). Our previous study explored a possible association between LEA and long-term adverse neurodevelopment in newborns, and the results indicated autism spectrum disorder (ASD) ( 10 , 11 ). ASD is a term used to describe a range of early-onset social communication deficits, and is also used on the repetitive sensory–motor behaviors related to genetics ( 12 ).…”
Section: Introductionmentioning
confidence: 99%